2021
DOI: 10.1007/s11356-021-13429-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of green growth in developed and developing countries

Abstract: Considering the need for environmental sustainability while ensuring economic growth and development by 2030, this study uses data on 123 developed and developing countries to examine factors that influence green growth. The empirical results show that economic development positively influences green growth. However, trade openness is detrimental to green growth. Regarding energy-related factors, we find energy consumption negatively affecting green growth, but renewable energy consumption significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 64 publications
(79 reference statements)
6
55
0
1
Order By: Relevance
“…In another study, Estevao ( 2020 ) proposed climate-friendly fiscal policies (e.g., green investment and environmental taxes) as a potential tool to promote economic growth during the crisis of COVID-19. Tawiah et al ( 2021 ) investigated various aspects of green growth, and concluded that developing countries should pay more attention to FDI and trade to manage the progress of green growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, Estevao ( 2020 ) proposed climate-friendly fiscal policies (e.g., green investment and environmental taxes) as a potential tool to promote economic growth during the crisis of COVID-19. Tawiah et al ( 2021 ) investigated various aspects of green growth, and concluded that developing countries should pay more attention to FDI and trade to manage the progress of green growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GHG emissions, i.e., emissions were positively impacted by the gross domestic product growth that matches, i.e., GDP. When it comes to per capita emissions of greenhouse gases and energy security, countries that use more energy face similar issues as other countries that use more energy ( Hao L. N. et al, 2021 ; Tawiah et al, 2021 ). Fossil fuel subsidies have been linked to higher GHG emissions and decreased energy security in both developed and less developed countries, according to numerous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies are analyses of statistical inferences of countries or a country studied in isolation. There are many studies covering various economies [28][29][30][31][32][33][34], for example [35][36][37][38]. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [35] conducted a study covering 123 countries, 146 countries for Ref. [36], 53 countries for Ref.…”
Section: Discussionmentioning
confidence: 99%